Herpes virus OsHV‐1 and the protist Perkinsus marinus modify the expression of the Down syndrome cell adhesion molecule gene in gill and mantle of Crassostrea spp. (21st September 2018) - Arzeta‐Pino, Lilián; Acosta, Armando; Sarmiento, Maria E.; Rojas‐Contreras, Maurilia; Rodríguez‐Jaramillo, Carmen; Vázquez‐Juárez, Ricardo
Abstract: The Down syndrome cell adhesion molecule (Dscam) gene in invertebrates encodes numerous isoforms derived by alternative splicing as a pathogen‐specific response. The role of Dscam in immune system responses has been established in fruit fly, mosquito, shrimp, crab, and crayfish, among other arthropods. In molluscs, this gene has not yet been clearly identified, and more importantly, its function has not been elucidated. The present study examined Dscam expression in Crassostrea gigas (CgDscam) and Crassostrea corteziensis (CcDscam) infected with Ostreid herpesvirus type 1 (OsHV‐1) and Perkinsus marinus, respectively, through in situ hybridization and quantitative PCR. The consensus coding sequences for CgDscam and CcDscam showed the same organization of domains identified in other taxonomic groups. Furthermore, conserved regions from the signal peptide to Ig1 and from FNIII6 to the cytoplasmic tail were identified. The Dscam transcript was detected in gills and mantles of both species. The hybridization signals were remarkable in infected tissues. QPCR analysis showed higher Dscam expression levels in the infected gills of both species, but in the mantle, no difference in CgDscam expression was observed between control and infected tissues. Moreover, CcDscam expression was inhibited in infected tissue. These results suggest that Dscam could be directly involved in bivalve immune responses.